Mathematics of investment - Abao, Zenon R.; Guhao, Eugenio S. Jr.;Marribay, Jose B. ;Zorilla, Roland S. ;Mendoza, Violeta C. ;Esller, Beda H. ;Partible, Fe G. ;Vila, Aurora E. (Mandaluyong City, Philippines : Books Atbp. Publishing Corp, 2008)
This book is written for use by college students to provide a strong and firm foundation of the general principles and application of mathematics in the fields of international hospitality management , tourism, business, economics, banking and finance, investment, insurance and accounting.
Chapter 1. Simple Interest -- Chapter 2. Compound Interest -- Chapter 3. Mathematics of Annuities -- Chapter 4. Annuities: General Case -- Chapter 5. Amortization -- Chapter 6. Bonds -- Index of Tables -- Bibliography.
Includes bibliographical references.
Keywords: INVESTMENTS